Molecular simulations of methane hydrate crystal structure and spectroscopic properties - Martos Villa, Rubén; Saínz Díaz, Carlos I.; Mata Campo, Maria Pilar (Sociedad Española de Mineralogía, 2020)
Congreso SEM-SEA 2012, reunión conjunta de las sociedades españolas de Mineralogía (XXXII Reunión) y Arcillas (XXII Reunión), celebrado en Bilbao entre el 27 y 30 de Junio de 2012 Gas hydrates are crystalline compounds consisting of gas molecules encaged in cavities of a hydrogen-bonded network of water molecules. Gas hydrates are characterized by the general formula X·DH2O, where X is the guest molecule within a water cage, and D! is the hydration number per guest molecule. Three different gas hydrate structures can be found: sI, sII and sH (Sloan, 1998). Cubic sI structure consists of 46 water molecules per unit cell, forming two dodecahedron (small 512) and six tetradecahedron (large 51262) cages (Fig. 1) and is formed when small guest molecules such as methane are trapped. Methane hydrates are found in permafrost regions and sediments of the ocean floor in outer continental margin regions where medium pressures and low temperatures can be reached (Kvenvolden and Rogers, 2005). Gas Hydrates are important on Earth´s system because hydrate decomposition would cause the release of methane into atmosphere (high greenhouse gas) causing great impact on Earth´s climate, dramatically increasing the temperature of the planet. On the other hand, these natural gas hydrates are seen as a potential major energy resource Departamento de Ciencias de la Tierra, Universidad de Cádiz, España Instituto Andaluz de Ciencias de la Tierra, Consejo Superior de Investigaciones Científicas, España Instituto Andaluz de Ciencias de la Tierra, Universidad de Granada, España Unidad de Tres Cantos, Instituto Geológico y Minero de España, España Junta de Andalucía, España